Ériger des pierres pour certains défunts en pays gewada (Éthiopie) - Jean-Paul Cros (OpenEdition, 2020)
Among the Gewada of southern Ethiopia, the deceased pogolho (customary chief), who was also a hasale (hero), is buried in the middle of a thornwood, in a shaft-like grave. This one is covered with a circular platform and indicated by a small standing stone put up in the ground. A few weeks later a ceremony takes place, made of songs and dances, which leads to the erection of a first stele on the tomb of the deceased, then another one on a reserved area in the extension of three other ones erected beforehand in honor of three pogolho. It was during the commemorative phase of the funeral of this important figure, punctuated by various rituals, that we could be present. The observations reported in this article are the work of archaeologists who had the opportunity to describe the context and the methods of erection of monoliths by one of the rare populations in the world who continues this practice even today. The role and importance attributed by the Gewada to these stelae, standing alone or in line, calls a great caution in interpreting those of the past, particularly European standing stones, whose raison d’être is unknown.